daughterless is essential for neuronal precursor differentiation but not for initiation of neuronal precursor formation in Drosophila embryo. - Vassin, H.; Brand, M.; Jan, L.Y.; Jan, Y.N. (Development, 1994)
The first steps of neuronal precursor formation require several genes that encode transcription regulators with the helix-loop-helix (HLH) motif, including the proneural genes of the achaete-scute complex AS-C (achaete (ac), scute (sc) and lethal of scute (l'sc)) and daughterless (da). The da protein dimerizes with AS-C products in vitro to form DNA-binding proteins. Previous studies have shown that the AS-C genes are expressed initially in discrete clusters of ectodermal cells (the proneural clusters) and then more strongly in the neuronal precursors that arise from these clusters and delaminate from the epidermal layer. In this paper, we studied the distribution of da protein with an antibody raised against Da. We found that Da is ubiquitously but non-uniformly distributed. Within the ectodermal layer, its level is neither elevated (as in the case of AS-C genes) nor reduced (as in the case of emc product) in the proneural cluster. It is, however, at higher levels in many neuronal precursors. We further studied the requirement of da in neuronal precursor development by using a variety of markers for neuronal precursors. Our results reveal the existence of at least two stages in neuronal precursor formation. da is not required for the initial appearance of nascent neuronal precursors but is required for these cells to express multiple neuronal precursor genes and to produce the normal number of neurons.